Understanding the driver of customer purchase decision : The role of customer engagement and brand attachment in Batik Products - Ardiyansyah, Rifal; Febrianti, R. Adjeng Mariana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Engagement has been recognized as one of the most influential aspects of an organization or company. It originally emerged as a concept in the organizational behavior and human resource management literature, as it is known to predict individual commitment, extra-role behavior, and other positive outcomes in organizations. The purpose of this study is to understand the influence of customer engagement and brand attachment in increasing purchase decision of customers. This study is using quantitative approach, with the population of customers of batik products in Sleman and Bantul, two regencies in Yogyakarta, Indonesia. The total number of samples is 115 respondents, which is selected using purposive sampling method. The data is collected through distributing questionnaire using online platforms, which is then analyzed using descriptive analysis and path analysis. The results indicate that customer engagement has an influence on brand attachment, brand attachment has an influence on purchase decision, and that brand attachment mediates the influence of customer engagement on purchase behavior.